Environment-specific shell shape variation in the boring mytilid Leiosolenus patagonicus. Issue 2 (7th February 2017) - Márquez, Federico; Frizzera, Antonella C.; Vázquez, Nuria
ABSTRACT: Environmental conditions induce phenotypic responses (behavioural, morphological and physiological) in many marine species. The boring mytilid Leiosolenus patagonicus inhabits different types of substrata, such as sandstone intertidal and hard subtidal substrata (here called 'lifeless-substratum') and shells of bivalve species (here called 'live-substratum'), where they are exposed to different restrictions in their growth. We used geometric morphometric methods to compare the contour shell shapes from each type of substratum (live and lifeless) since we expected the body shape to differ between individuals from these different substrata. The results showed that the shell shape depends on the type of substratum where the larvae recruit. The mean shell shapes of individuals from the live-substratum are more slender than those of the individuals growing inside the lifeless-substratum. Individuals from live-substratum can adapt their phenotype depending on the oyster's anti-parasitism responses, while in lifeless-substratum they are able to build their own refuges.